Interpretasi Nilai Kemanusiaan dalam Lirik Lagu Heal The World Karya Michael Jackson: Analisis Hermeneutika - Muhamad Rafi Alfarizi; Alya Nurul Syahidah Syahidah; Anjani Dwi Maharani Priatna Priatna; Iqbal Tazkiya Imani Imani; Muhammad Syauqi Asy-syafiq Fahrurrazi Fahrurrazi; Welsi Damayanti Damayanti (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2025)
This study aims to interpret the humanitarian values in the lyrics of Michael Jackson's song "Heal the World" through a hermeneutical approach. Music is seen as a medium capable of conveying moral, social, and humanitarian messages, so analyzing the lyrics is crucial to understanding the deeper meaning the songwriter intended to convey. Using a qualitative descriptive method with hermeneutical analysis, this study examines the lyrics based on Wilhelm Dilthey's concepts of Erlebnis (life experience), Ausdruck (expression), and Verstehen (understanding). Data were obtained through listening to the song, taking notes on the lyrics, and understanding its grammatical structure. The results show that the lyrics of "Heal the World" contain strong humanitarian messages, such as empathy, solidarity, peace, and hope, reflected through the songwriter's inner experiences and evocative use of language. This research contributes to the study of music and humanitarian values, particularly in understanding music as a means of conveying universal moral messages.